2016
DOI: 10.1016/j.micres.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Novel strategy to detect and locate periodontal pathogens: The PNA-FISH technique

Abstract: Purpose: We aim to develop peptic nucleic acid (PNA) probes for the identification and localization of Aggregatibacter actinomycetemcomintans and Porphyromonas gingivalis in sub-gingival plaque and gingival biopsies by Fluorescence in situ Hybridization (FISH).Methods: A PNA probe was designed for each microorganism. The PNA-FISH method was optimized to allow simultaneous hybridization of both microorganisms with their probe (PNA-FISH multiplex). After being tested on representative strains of P. gingivalis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The latter demonstrated an increase in A. actinomycetemcomitans colony-forming units, which correlated with its presence in the tissue and in the periodontal pocket [165]. In situ hybridization studies have detected A. actinomycetemcomitans in epithelial cells from the lining gingival crevice [166] or in close relationship with the polymorphonuclear infiltrate of the pocket [167]. By quantitative real-time PCR of gingival tissue lysates, it was shown that A. actinomycetemcomitans is present at a higher prevalence in tissues of younger patients with aggressive periodontitis as compared to chronic periodontitis or health [168].…”
Section: Localization In Pocket and Tissuementioning
confidence: 91%
“…The latter demonstrated an increase in A. actinomycetemcomitans colony-forming units, which correlated with its presence in the tissue and in the periodontal pocket [165]. In situ hybridization studies have detected A. actinomycetemcomitans in epithelial cells from the lining gingival crevice [166] or in close relationship with the polymorphonuclear infiltrate of the pocket [167]. By quantitative real-time PCR of gingival tissue lysates, it was shown that A. actinomycetemcomitans is present at a higher prevalence in tissues of younger patients with aggressive periodontitis as compared to chronic periodontitis or health [168].…”
Section: Localization In Pocket and Tissuementioning
confidence: 91%
“…In addition to q-PCR, which has been a widely used technique in analysing environmental and clinical microbiological samples, epifluorescence microscopy based methods also offer a faster and reliable alternative for monitoring polymicrobial biofilm communities. In particular, PNA-FISH effectively extends epifluorescence microscopy, allowing for a rapid discrimination, location and/or enumeration of bacterial populations in polymicrobial communities 40 , 47 , 67 74 . In our study, to make biofilm-cells counts easy and homogeneous (which likely facilitates in the case of thick and more dense biofilms), PNA-FISH assay was performed ex situ to quantitatively monitor bacterial populations in the multispecies consortia 69 , 70 .…”
Section: Resultsmentioning
confidence: 99%
“…During the past 5 y, several groups have examined bacterial infection in periodontitis-affected gingival tissues using diverse methods, including Gram staining, in situ hybridization using digoxigenin-labeled probes, in situ hybridization using fluorescence-labeled peptic nucleic acid probes, and immunohistochemistry using antibodies specific to each bacterial species or virulence factors (Table). Regardless of the methods used, P. gingivalis, A. actinomycetemcomitans, T. forsythia, T. denticola , and Fusobacterium nucleatum were detected intracellularly in the junctional/sulcular epithelium and extracellularly in the disrupted epithelium and the area of inflammatory infiltration of the lamina propria (Mendes et al 2016; Listyarifah et al 2017; Baek et al 2018; Engstrom et al 2018; Rajakaruna et al 2018). Two of 3 studies that compared the presence of bacteria in periodontitis-affected tissues with that in control tissues reported increased bacterial infection in the periodontitis tissues, but 1 study reported comparable levels of P. gingivalis and A. actinomycetemcomitans in the periodontitis tissues compared with the healthy tissues (Choi et al 2014; Listyarifah et al 2017; Engstrom et al 2018).…”
Section: Bacterial Invasion Of Gingival Tissue In Periodontitismentioning
confidence: 99%